"Through a Glass, Darkly": Lessons Learned Starting over as an Electronic Resources Librarian. Issue 3 (17th November 2021) - Brown, Daniel
ABSTRACT: This article examines the experience of a starting electronic resources librarian, who transitioned to the role after working for a vendor and as a faculty member. The author's experience demonstrates the complex, often ambiguous nature of the role, as supported by the professional literature. The article concludes with a call for greater product support and transparency on the part of vendors. Although anecdotal, the author's experience should interest new ERLs as well as library staff and vendors with whom they communicate. It should also interest those who are considering so-called "alternative academic" (non-professorial) careers with their doctoral degrees.